2014
DOI: 10.4103/1947-2714.125863
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus among tuberculosis patients in Urban Puducherry

Abstract: Background:Diabetes and Tuberculosis often present together and complicate each other at many levels. A collaborative framework for care and control of diabetes and tuberculosis developed by World Health Organisation and International Union against Tuberculosis and Lung Diseases emphasizes routine bi-directional screening for the two diseases.Aims:The study was to assess the prevalence of diabetes in tuberculosis patients currently on treatment.Materials and Methods:This facility-based cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
15
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 12 publications
10
15
1
1
Order By: Relevance
“…The association of increasing age with diabetes evident from the study is consistent with past studies conducted in India [17,23,24] and China [25]. Increasing age has been established to be associated with both TB and diabetes through previous studies [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…The association of increasing age with diabetes evident from the study is consistent with past studies conducted in India [17,23,24] and China [25]. Increasing age has been established to be associated with both TB and diabetes through previous studies [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…The patients with TB-T2DM were 10 years older than those with TB only. This difference can be explained by the parallel increase of the prevalence of T2DM with age, as has been previously reported (Delgado-Sanchez et al, 2015;Hongguang et al, 2015;Perez-Navarro et al, 2015;Raghuraman, Vasudevan, Govindarajan, Chinnakali, & Panigrahi, 2014). Our study supports the concept that family history of diabetes (reported in 68% of patients with TB-T2DM, OR 5.04, IC 95% 3.4, 7.4, p< 0.001) is a risk factor for development of TB (Ogbera et al, 2015;PerezNavarro et al, 2015;Chittoor et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…[ 18 ] This result also in line with research conducted in India found that TB patients with comorbidities leading to delayed sputum conversion primarily occurred in communities with low social class. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%